Communicating the Corporate Social Responsibility on the Company Website: A Study Conducted on WRAP Certified Apparel Manufacturers in India - Sanil, Hishan S.; Ramakrishnan, Suresh (International Journal of Economics and Financial Issues, 2015)
Business sustainability becomes an important issue in the present competitive business world. Therefore, organisation has to commit to Corporate Social Responsibility (CSR) as a part of their business strategy. One of the important components of this strategy is the effective and transparent communication about CSR. This study examines the CSR communication in the company websites undertaken by the WRAP (Worldwide Responsible Accredited Production) certified apparel manufacturers in India. It also analyses whether the companies have mentioned regarding the Companies Act 2013 in their company website. The purposive sampling method was used and only the WRAP certified apparel manufacturing companies were included in the study. Data was analysed using the descriptive statistics. The study includes 180 WRAP certified apparel-manufacturing companies in India. Among them 118 were Gold rated, 2 silver rated and 60 Platinum rated. The finding shows that only 48% of these companies had CSR information in their company websites. In addition, only 3% of these companies gave some information about the companies' act 2013 in their company websites. In other words, majority of the firms in the apparel industry fail to disseminate the CSR information via website. Furthermore, only a few firms have mentioned the companies act 2013 in their websites. In general, the lack of proactive CSR communication among the apparel firms in India is perceptible. However, it does not necessarily show the absence of CSR action in these apparel-manufacturing companies. Keywords: Corporate Social Responsibility, Communication, Apparel Industry, India JEL Classifications: M00